Proceedings of the 6th International Conference on Computational Methods in Structural Dynamics and Earthquake Engineering (COM 2017
DOI: 10.7712/120117.5625.18529
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Response of a Rigid Slab Supported by Four Rigid Cylinrical Rocking and Wobbling Columns

Abstract: Abstract. Letting columns uplift has been proposed as an earthquake response modification

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Based on the assumptions presented in Section 3, the equations of motion of the system are lefttrueθ¨=truep̂2sinαθ+cosαθu¨ggcosφ+v¨ggsinφ++trueφ̇2leftsinθsin2α4γ+32+cosαsinα4γ+11+cosθ2cos2θ+sinθcosθ43cos2α54sin2α+4γcos2αsin2α1248γ+15+cos2a lefttrueleft43cos2a54sin2α+4γcos2αsin2αsin2θ+3+8γ1cosθsin2α+2sinαcosαsinθ1+4γ1cosθφ¨++left3+8γsin2αsinθ+8…”
Section: Description Of the Proposed 3d Modelmentioning
confidence: 99%
“…Based on the assumptions presented in Section 3, the equations of motion of the system are lefttrueθ¨=truep̂2sinαθ+cosαθu¨ggcosφ+v¨ggsinφ++trueφ̇2leftsinθsin2α4γ+32+cosαsinα4γ+11+cosθ2cos2θ+sinθcosθ43cos2α54sin2α+4γcos2αsin2α1248γ+15+cos2a lefttrueleft43cos2a54sin2α+4γcos2αsin2αsin2θ+3+8γ1cosθsin2α+2sinαcosαsinθ1+4γ1cosθφ¨++left3+8γsin2αsinθ+8…”
Section: Description Of the Proposed 3d Modelmentioning
confidence: 99%
“…They concluded that even though the 2D approximation is not conservative, 3D objects still present remarkable stability when excited dynamically. Rajah et al (2017) extended the 3D model of Vassiliou et al (2017b) to study the behavior of a slab supported on wobbling columns. As in the case of the planar rocking frame, the presence of the slab increases the stability of the system, even though it raises its center of mass.…”
Section: Rocking Piers Conceptmentioning
confidence: 99%